Pengaruh Environmental Policy, Environmental Pollution, Environmental Energy, Dan Environmental Financial Terhadap Kualitas Laba - lidya primta surbakti (Universitas Teuku Umar, 2023)
This research is a quantitative research and the aim of this research is to empirically examine the influence of environmental policy, environmental pollution, environmental energy, and environmental finance on earnings quality and profitability, leverage, and company size as control variables. Earnings quality is measured using real earnings management as a measurement.This study uses secondary data, namely non-financial companies listed on the Indonesia Stock Exchange for the period during 2019-2021 . The total sample in this study was 198 samples using the panel data regression analysis method and using data analysis with STATA. The research results show that environmental policy, environmental pollution, environmental energy, and environmental financial no significant effect on earnings quality. But there is a significant and positive effect on the control variables including: profitability, company size and debt ratio on earnings quality. The limitation of this study is that the population is non-financial companies and only measures the disclosure of sustainability reports only from pollution, energy, finance and policy. The practical implication of this research is that the more sustainability report disclosures made by companies, including: policies, pollution, energy and finance, no significant effect on the quality of earnings in companies listed on the IDX, and the increasing profitability, debt ratios and company size, the higher earnings quality, so that investors can consider profitability, company size and debt ratio in investment decisions because one of the considerations of investors is profit. The original value of this research is that this research measures more specific environmental reporting disclosures including: environmental policy, environmental pollution, environmental energy, and environmental financial and earnings quality measurement in this study uses real earnings management with the Cohen and Zarowin (2010) model which is still rarely used.